(untitled) (Journal of Hama University, 2024)
This study was conducted on three natural populations of the carob tree (Ceratonia siliqua L.) in Latakia Governorate (Qarah Falah (Q), Jibul (G) and Snoubr Jablah (S)), to determine the difference and correlation in growth characteristics and productivity in the research sites between carob trees on Basis (crown area/m2, crown height/m, crown volume/m3), (number of pods/tree, weight of pods kg/tree, number of seeds per pod and weight of seeds g/tree). Significant differences were found according to the results of the research, as the carob trees excelled at the Qarah Falah site in terms of growth and productivity characteristics, followed by the Snoubr Jableh tree site, and the last place was ranked by Jibul. The growth and productivity characteristics of the carob trees were also associated with the weight of seeds with significant and positive relationships according to the regression coefficient in the research sites, and thus it can be Conduct future studies on fewer characteristics and benefit from this study in breeding programs to obtain promising and distinguished varieties with high growth and productivity characteristics.